2006
DOI: 10.1007/s00383-006-1824-3
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired regulatory mechanism of perioperative cytokine response in neonates

Abstract: The inflammatory reaction is known to be controlled in neonates. We clarified the characteristics of cytokine profile in neonatal patients and assess its clinical significance. Serum levels of interleukin (IL)-6 and IL-1 receptor antagonist (ra) were determined in 152 pediatric patients and 33 each of maternal and cord bloods. Supernatant IL-1ra levels of cultured monocytes and granulocytes stimulated with IL-1beta or LPS, and IL-1ra mRNA expression of granulocytes were assayed in 15 each of cord and healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The concentration of IL-6 in serum rose signifi cantly following surgery, achieving a peak value on POD 1. Such an IL-6 response to surgery is in agreement with previous reports in neonates and is similar to the response of adults but with a later peak concentration [8,9] . The reason for the delay in IL-6 response in neonates compared to adults could be the immature regulation of the cascade of host mediators in neonates [9] .…”
Section: Serum Concentration Of Il-6supporting
confidence: 92%
See 1 more Smart Citation
“…The concentration of IL-6 in serum rose signifi cantly following surgery, achieving a peak value on POD 1. Such an IL-6 response to surgery is in agreement with previous reports in neonates and is similar to the response of adults but with a later peak concentration [8,9] . The reason for the delay in IL-6 response in neonates compared to adults could be the immature regulation of the cascade of host mediators in neonates [9] .…”
Section: Serum Concentration Of Il-6supporting
confidence: 92%
“…In the study of Bolke et al, on the other hand, such an increase in IL-6 and CRP serum concentrations was only found in neonates after gastroschisis repair, but not after other types of abdominal and thoracic surgery [10] . More consistent are the reports on the increased serum concentrations of IL-8 in neonates after major abdominal and thoracic surgery [7,8] . The postoperative induction of another infl ammatory marker, procalcitonin (PCT), was studied mainly in adult patients, where PCT was shown to be signifi cantly increased after cardiac, major abdominal and thoracic surgery [11] .…”
Section: Introduction ▼supporting
confidence: 82%
“…Then, PMNs in Groups A and B were stimulated by tumor necrosis factor-alpha (TNF-␣) (10 ng/mL) and lipopolysaccharide (LPS; 100 ng/mL). PMNs were cultured in a humidified 5% CO 2 incubator with TNF-␣ or LPS at 37°C for 24 h. Our previous study revealed that the level of cytokine production by PMNs increased over time and reached a peak within a 24-h period [15]. In the present study, supernatants were collected and cytokine production (IL-1␣, IL-1Ra, IL-6, and IL-8) was analyzed using ELISA kits.…”
Section: Pmn Stimulation Model Assaysmentioning
confidence: 99%
“…PMN stimulation was based on our previously described procedure [15]. Approximately 1 ϫ 1 cm 2 of Seprafilm was placed (Group A) or not placed (Group B) in the medium.…”
Section: Pmn Stimulation Model Assaysmentioning
confidence: 99%
“…IL-6 showed fast response to surgical stress; this is in agreement with previous reports in neonates and adults. 2,5,15,19,20 Bölke et al did not find increasing plasma concentrations of IL-6 in neonates in general due to the absence of endotoxemia and subsequent mediator release. 14 Neonates with septic complications had significant higher IL-6 peak values than with the other groups, whereas no differences were obvious in PCT and CRP levels.…”
Section: Discussionmentioning
confidence: 92%